Rancang Bangun Sistem Penerimaan Santri Baru Berbasis Website Di Pondok Pesantren Al-Hadi Gresik - Nurfiana, Dwi; Yusup, Yusup; Prakoso, Satrio Agung (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research was conducted to design and develop a website-based New Student Admission Information System at Islamic Boarding School Tahfidzul Qur'an Al-Hadi Gresik. This research uses the waterfall method, which includes sequential analysis to implementation stages. The final results showed that this new information system can improve efficiency and accuracy in the process of admitting new students and support the operations of the pesantren. The system provides various benefits, including increased enrollment efficiency, reduced administrative errors, and more structured management of santri data. It is recommended to conduct further development and training for administrative staff to ensure optimal use of the system. Thus, it is expected that the New Student Admission Information System at Islamic Boarding School Tahfidzul Qur'an Al-Hadi Gresik can operate optimally.